Implementasi Low Power Mode Pada Perangkat Sistem Pendeteksi Dini Kebocoran Gas Menggunakan Atmega328p - Eko Hilmi Firmansyah; Dahnial Syauqy; Sabrian Rizqika Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
LPG (Liquefied Petroleum Gas) is an economic necessity that needed a day by day in the household. Precautions against the use of LPG can not be underestimated. Because the LPG may leak so that high-risk fire against the onset of gas equipment. By using a system of early detection of gas leakage, the anticipation towards high risk can be prevented much faster and easier to use. In order to make the device the system running efficiently, then the device in its application performance using low power to save power consumption. Saving is done so that the device can work in a relatively long period of time using the battery's energy source. Utilize low power performance at mikrokontroller ATmega328p expected give implementation needs the device on power consumption more efficient. The features are used i.e. sleep mode power down to turn off multiple sub systems on early detection system device gas leaks. Testing resulted in the conclusion that the system is running in accordance with the principles of its work. On testing reading sensor MQ-6 can take the data of gas is detected on the sensor. On testing the sensor reading FC-4 can read the value of digital data. On the power consumption of the device is able to suppress the flow of 23.54 from 157.02 mA with the application of the sleep mode power down.